Resveratrol Synergistically Promotes BMP9-Induced Osteogenic Differentiation of Mesenchymal Stem Cells - Yonghui Wang; Chao Xia; Yang Chen; Tianyuan Jiang; Yan Hu; Yanhong Gao (Stem Cells International)
Background. Mesenchymal stem cells (MSCs) differentiate into osteocytes, adipocytes, and chondrocytes. Resveratrol and bone morphogenetic protein 9 (BMP9) are known osteogenic induction factors of MSCs, but the effect of both resveratrol and BMP9 on osteogenesis is unknown. Herein, we explored whether resveratrol cooperates with BMP9 to improve osteogenic induction. Methods. The osteogenic induction of resveratrol and BMP9 on C3H10T1/2 cells was evaluated by detecting the staining and activity of the early osteogenic marker alkaline phosphatase (ALP). In addition, the late osteogenic effect was measured by the mRNA and protein levels of osteogenic markers, such as osteopontin (OPN) and osteocalcin (OCN). To assess the bone formation function of resveratrol plus BMP9 in vivo, we transplanted BMP9-infected C3H10T1/2 cells into nude mice followed by intragastric injection of resveratrol. Western blot (WB) analysis was utilized to elucidate the mechanism of resveratrol plus BMP9. Results. Resveratrol not only enhanced osteogenic induction alone but also improved BMP9-induced ALP at 3, 5, and 7 d postinduction. Both the early osteogenic markers (ALP, Runx2, and SP7) and the late osteogenic markers (OPN and OCN) were significantly increased when resveratrol was combined with BMP9. The fetal limb explant culture further verified these results. The in vivo bone formation experiment, which involved transplanting BMP9-overexpressing C3H10T1/2 cells into nude mice, also confirmed that resveratrol synergistically enhanced the BMP9-induced bone formation function. Resveratrol phosphorylated adenosine monophosphate- (AMP-) activated protein kinase (AMPK) and stimulated autophagy, but these effects were abolished by inhibiting AMPK and Beclin1 using an inhibitor or siRNA. Conclusions. Resveratrol combined with BMP9 significantly improves the osteogenic induction of C3H10T1/2 cells by activating AMPK and autophagy.